The Effect of Using Visual Accuracy Device on Spiking in Youth Volleyball - Atiya, Wessam; Satar, Khalil (Journal of Physical Education, 2022)
The research aimed at designing a device that simulate blocking in volleyball as well as designing special exercises using the designed device for developing visual accuracy in spiking in volleyball for youth players. The researchers used the experimental method on Al Senaa club players aged (15 – 17 years old. Visual accuracy was tested during spiking and treated using proper statistical operations to conclude that using special exercises with the device have a significant effect on the experimental group to improve visual accuracy of spiking. In addition to that, the researchers conclude that using special exercises have a significant role in achieving individual differences between the two groups in posttests in favor of the experimental group.